Investigation of manual material handling on musculoskeletal disorder at computer numerical control workstation / Nor Suliani Abdullah - Nor Suliani, Abdullah (2020)
Manual Material Handling (MMH) tasks have been recognized among the major source of work-related musculoskeletal disorder (WMSD) in automotive industry and they are commonly practiced at Computer Numerical Control (CNC) workstation. At this workstation, workers act as a material transfer device in the process of loading and unloading products from pallets to machines. The physical interaction of workers to machine is not self-chosen and workers are forced to follow the pace of running CNC machine. The worst situation happens when workers are required to operate more than one machine concurrently. The mismatch interaction between workers and machine exposes workers to awkward working posture which leads to high risk of WMSDs. Currently, investigation of MMH tasks at CNC workstation is still scarce. Thus, this study aims to determine the prevalence of WMSDs among MMH workers at CNC workstation and to find the relationship of loads to energy expenditure and back postural angles. The methodology in this study comprises an industrial survey and a series of experimental tasks. A total of 113 workers from automotive industry participated in the industrial survey while 14 workers and 14 novices participated in experimental tasks. The results of industrial survey reveal that 78.8% of the workers experience the symptoms of WMSDs on various regions of their body. The highest prevalence of the WMSDs is at the lower back with 85.8%. The significant factors that are associated with the WMSDs are bending the trunk slightly forward with hands above the knee level, twisting the trunk (over 45°) while bending sideways and lifting object less than 3kg. The experimental results reveal that the maximum energy expenditure is found when novice (bending: 4.32kcal/min; squatting: 4.95kcal/min) and worker (bending: 3.64kcal/min; squatting: 4.39 kcal/min) performed 3 kg load tasks. Novice has 23.73% and 16.53% higher of energy expenditure compared to worker for 1kg load tasks in bending and squatting respectively. Novice also has 15.74% and 11.31% higher energy expenditure for 3kg load iii tasks in bending and squatting respectively. Load is discovered to positively correlates with energy expenditure in both subjects and both postures. Load also have positive correlation with back postural angles in many tasks whereas has negative correlation with back postural twisting angles. The most correlated back postural angles with load occurs at Task 10 which refers to lowering task. The deviation of back postural angle increases as load increases. Novice exhibits higher back postural angles compared to worker. The result reveals that the optimum working posture is at neutral trunk posture with the lowest energy expenditure in which the deviation of trunk flexion angles fall within a range of 0° and 20° from the sagittal plane.